2022
DOI: 10.1371/journal.pone.0269840
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence older patients’ participation in clinical communication within developed country hospitals and GP clinics: A systematic review of current literature

Abstract: Background Engaging older adults in clinical communication is an essential aspect of high-quality elder care, patient safety and satisfaction in hospitals and GP clinics. However, the factors that influence older adults’ participation during their appointments with health professionals from the older patient’s perspective remain under-investigated. Objectives We aimed to fill this knowledge gap by reviewing research articles that have examined older patients’ involvement in clinical communication. In doing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In contrast to our findings, a study exploring health care utilization for headache disorders found the majority of visiting paramedical professionals for their problems [ 53 ]. This may be due to differences in accessibility of health services, health information, and the perceived credibility and trustworthiness of studied participants [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, a study exploring health care utilization for headache disorders found the majority of visiting paramedical professionals for their problems [ 53 ]. This may be due to differences in accessibility of health services, health information, and the perceived credibility and trustworthiness of studied participants [ 54 ].…”
Section: Discussionmentioning
confidence: 99%